2021
DOI: 10.1002/pat.5424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terpene alcohol dopant on the morphology and electro‐optical properties of polymer‐dispersed liquid‐crystal composite films

Abstract: Terpenes are a large class of hydrocarbon compounds derived from isoprene, which can be produced by plants or emitted by insects. Terpene alcohols contain double bonds that may affect the addition polymerization, and hydroxyl groups that can promote the network crosslinking density during the formation of polymer-dispersed liquid-crystal (PDLC) composite films. In this work, effects of different terpene alcohol dopant on the morphology and electro-optical properties of PDLC films are systematically investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Figure S4 showed that with the introduction of polymer walls, the t on decreased and the t off increased because the size of LC droplets increased (consistent with Figure S3). 17,35,36 Figure 3 illustrated that the polymer walls could significantly improve the stability of reverse-mode PSLC films. The sparse and fine polymer networks were more easily destroyed after multiple cycles for the films without polymer walls.…”
Section: Effect Of the Introduction Of Polymer Walls On Electro-optic...mentioning
confidence: 99%
“…Isomers with the same chemical formula but different structure might have different influences on PDLC films 44 . Nevertheless, the research is limited.…”
Section: Resultsmentioning
confidence: 99%